Social responsibility of startups - BELAA, Djaouida (Finance and Business Economies Review, 2023)
The application of corporate social responsibility in its comprehensive concept gives the benefit to all stakeholders involved in the internal and external environmental work. However, the privacy of startups and the problems that suffers from may hinder the realization of this benefit what Holds back the sustainable development strategy. Accordingly, this study aims to determine the nature and the importance of startups exercising social responsibility, to clarify the role of social responsibility in raising the market value of startups and in the formation of self-protection for it in crisis conditions, in addition to its contribution to building and enhancing a positive mental image of it. Therefore, the descriptive and analytical approach was adopted to present and realize these aims.